Predestination and Freewill in the Bible and the Qur'an: a Comparative Appraisal - Opeloye, M. O. (2014)
Predestination and Free-Will are perhaps the most controversial theological concepts. The theological problem of whether or not divine will determines humans’ actions and salvation remains unresolved. Many Christians as well as Muslims are of the view that prior to creation, God had predestined the fate of man. Others hold the opposite view that man is the determiner of his fate. The Jabarites among the Muslims and the Calvinists among the Christians believe in the doctrine of predestination while the Qadarites and Mu'tazilites among the Muslims and the Pelagians in Christianity believe in Free-Will. It is paradoxical that each group finds justification for its views from the scriptures which is to say that the two concepts' are affirmed therein. In the light of this, it is generally believed that the scriptures contain contradictory teachings on these subjects. In our view, this results from lack of proper understanding of the scriptural teachings on predestination and free-will. This paper therefore attempts to examine the context of predestination and free-will in the Bible and Qur'an with a view to justifying the extent to which the teachings of the two scriptures on the two concepts are mutually complementary rather than contradictory as it is often thought.